2004
DOI: 10.1128/jvi.78.17.9154-9163.2004
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Calcium and pH Requirements for Proteolytic Processing of the Hendra Virus Fusion Protein

Abstract: Proteolytic cleavage of the Hendra virus fusion (F) protein results in the formation of disulfide-linked F 1 and F 2 subunits, with cleavage occurring after residue K 109 in the sequence GDVK2L. This unusual cleavage site and efficient propagation of Hendra virus in a furin-deficient cell line indicate that the Hendra F protein is not cleaved by furin, the protease responsible for proteolytic activation of many viral fusion proteins. To identify the subcellular site of Hendra F processing, Vero cells transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 67 publications
8
68
0
Order By: Relevance
“…In agreement with our findings, Pager et al (40) recently reported that cleavage of the Hendra virus F protein is also sensitive to increases in intracellular pH levels. Because the Hendra virus F protein also contains a YSRL endocytosis motif in its cytoplasmic tail (6), our results strongly suggest that the closely related Hendra virus F protein is also cleaved by a pH-dependent endosomal protease.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with our findings, Pager et al (40) recently reported that cleavage of the Hendra virus F protein is also sensitive to increases in intracellular pH levels. Because the Hendra virus F protein also contains a YSRL endocytosis motif in its cytoplasmic tail (6), our results strongly suggest that the closely related Hendra virus F protein is also cleaved by a pH-dependent endosomal protease.…”
Section: Discussionsupporting
confidence: 83%
“…Specific F protein mutants were subcloned into the pCAGGS expression plasmid as previously described (28). Wt HeV F and G (also provided by Lin-Fa Wang) genes were ligated into pCAGGS as described previously (29).…”
Section: Plasmidsmentioning
confidence: 99%
“…1), including heptad repeats (HR) critical for promotion of membrane fusion (reviewed in reference 5) and posttranslational cleavage of the precursor form (F 0 ) to the fusogenic heterodimer, F 1 ϩF 2 (13). The Hendra virus F ectodomain contains five N-X-S/T motifs for the potential addition of N-linked carbohydrates, two in F 1 and three in F 2 .…”
mentioning
confidence: 99%
“…While N485 was previously identified as a potential site for N-linked glycosylation (9), a proline at position 486 should preclude N-linked glycosylation. To analyze expression and mobility, the wildtype (wt) or mutant Hendra virus F genes in the pCAGGS expression plasmid (12) were transfected into Vero cells and metabolic labeling and immunoprecipitation were performed as previously described (13). Samples were separated on a 10% polyacrylamide gel.…”
mentioning
confidence: 99%